Hungarian Monitoring, 3 May 1990 . [Magyar rádiófigyelő], 1990. május 3 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - The new Latvian Parliament's first session - The Lithuania economy has begun to stagnate - Bush is worried about Gorbachev's future Domestic Affairs: - Statutory meeting of the new Hungarian Parliament - Formation of parliamentary committees - Hungarian Democratic Forum (MDF)-Alliance of Free Democrats (SZDSZ) agreement on modifying the constitution - Negotiations about the election of the president - Disciplinary procedure against two functionaries of the Hungarian Populist Party - Cornelia Doina about the Hungarian university in Romania - György Krassó's unconventional tent protest in front of the Parliament building Economy: - The Budapest-Vienna World Exposition fund established - DuPont opens factory in Hungary - Struggle for the Hungarian telephone market Külpolitika: - Összeült az új lett törvényhozás - Romlik Litvánia gazdasági helyzete - Bush elnök aggódik Gorbacsov jövője miatt Belpolitika: - Alakuló ülést tart az Országgyűlés - Parlamenti bizottságok megalakulása - MDF-SZDSZ megállapodás az alkotmány módosításáról - Tárgyalások a köztársasági elnök választásáról - Fegyelmi eljárás a Magyar Néppárt két funkcionáriusa ellen - Doina Cornea a romániai magyar egyetemről - Krassó György rendhagyó táborozása a parlament előtt Gazdaság: - A Világkiállítási Alap felállítása - A Dupont cég vállalatot alapít Magyarországon - Harc a magyar telefonpiacért